Model Bimbingan Dan Konseling Komprehensif dalam Meningkatkan Akhlak Mahasiswa - Siti Chodijah (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2016)
Guidance and counseling become one of the pillars to overcome bad morality and to improve good morals. One form of guidance and counseling in universities in accordance with the conditions in Indonesia is comprehensive guidance and counseling covering academic, social-personal, and career. This paper aims to develop a model of guidance and counseling in Islamic Religious College for students, based on guiding concepts that have been done by academic supervisors with categorization aspects of trust, tawadhu, qana'ah and tawakal. The method used in this research is research and development (R & D) to UIN Sunan Gunung Djati Bandung students. The result is the effort of academic advisors in improving the noble character of the students through the guidance is classified as less effective and needs to be improved.